CHD7 mutations are not a major cause of atrioventricular septal and conotruncal heart defects. Issue 12 (24th September 2014) - Corsten‐Janssen, Nicole; du Marchie Sarvaas, Gideon J.; Kerstjens‐Frederikse, Wilhelmina S.; Hoefsloot, Lies H.; van Beynum, Ingrid M.; Kapusta, Livia; van Ravenswaaij‐Arts, Conny M.A.
<x xml:space="preserve">Abstract</x> Since 2004, CHD7 mutations have been a known cause of CHARGE (Coloboma, Heart defects, Atresia of choane, Retardation of growth and development, Genital hypoplasia, Ear anomalies) syndrome, but the full clinical spectrum of CHD7 mutations is only now gradually emerging. CHD7 mutations have been identified in patients who do not fulfill the clinical criteria for CHARGE syndrome and in patients with overlapping syndromes. Variable congenital heart defects occur in the majority of patients with CHD7 mutations, with an overrepresentation of atrioventricular septal defects and conotruncal heart defects. This prompted us to study CHD7 in 46 patients with these heart defects and one other feature of CHARGE syndrome. We identified two CHD7 variants that were inherited from a healthy parent (c.3778 + 17C > T, c.7294G > A), but no pathogenic CHD7 mutations. We conclude that CHD7 mutations are not a major cause of the atrioventricular septal defects and conotruncal heart defects, not even if one extra phenotypic feature of CHARGE syndrome is present. Therefore, CHD7 analysis should not be performed routinely in this group of patients. However, we do recommend adding CHD7 to massive parallel sequencing gene panels for diagnostic work in patients with syndromic heart defects. © 2014 Wiley Periodicals, Inc.